2023
DOI: 10.3390/math11122761
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Asset and Liability Management of Banks with Minimum Possible Changes

Abstract: Asset-Liability Management (ALM) of banks is defined as simultaneous planning of all bank assets and liabilities under different conditions and its purpose is to maximize profits and minimize the risks in banks by optimizing the parameters in the balance sheet. Most of the studies `and proposed models in the ALM field are based on an objective function that maximizes bank profit. It is not easy to apply changes in these models in order to reach the optimal values of the parameters in the balance sheet. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 168 publications
0
2
0
Order By: Relevance
“…Peykani et al [13] introduced a Linear Programming (LP) model that integrates constraints to attain optimal values for parameters within the balance sheet. This model is consistent with the goals of Asset Liability Management (ALM), taking into account constraints related to the system, balance sheet, and regulations.…”
Section: Related Workmentioning
confidence: 99%
“…Peykani et al [13] introduced a Linear Programming (LP) model that integrates constraints to attain optimal values for parameters within the balance sheet. This model is consistent with the goals of Asset Liability Management (ALM), taking into account constraints related to the system, balance sheet, and regulations.…”
Section: Related Workmentioning
confidence: 99%
“…Similarly, Batrancea [2] (p. 260) indicated that commercial banks play an essential role in mobilizing and distributing funds by loans and deposits to their clients. Accordingly, the banking system can be identified as one of the most important economic sectors [3] (p. 2761), where banks play an active role in the financial markets of any nation [4] (pp. [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60].…”
Section: Introductionmentioning
confidence: 99%
“…The importance of economic policies in economic development, on the one hand, and the effects of wrong policies and their destructive power on the other hand, make attention to how economic policies are applied and how they work always be the main topic of economists' analysis [1][2][3][4]. From the point of view of economic scientists, the effect of applied policies is different and how and by changing which variables and markets affect the target variables of the policy [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%